Estudio de factores de riesgos ergonómicos en los puestos de trabajo administrativo de la empresa EMAPALA EP. - Rumipamba Romero, Ronald Alexander (2022)
Occupational health and safety is a key factor in the company to prevent negative consequences in work activity. The present research work deals with the identification and evaluation of the ergonomic risk factors to which the worker of the administrative area of the company EMAPALA EP is exposed. By applying the observation and the ergonomic survey, it was possible to identify the risks, having as a greater risk the inadequate postures and the repetitive movements, for the evaluation of postures, the RULA method was applied, obtaining as a result that jobs 2 and 8 have a performance level of 3, where the redesign of the task is recommended; with the OWAS method, 7 postures of a single job were evaluated, giving us as a result that posture 6 is the most critical and corrective actions are recommended; finally, the OCRA Check list method was used to evaluate repetitive movements of the 15 jobs, obtaining as a result the 10th and 14th positions as critical, where improvements in the jobs are recommended. According to the results obtained, it can be determined that there are moderate risks, for this reason, an ergonomic risk prevention plan is proposed, detailing the preventive measures and an active break procedure that workers must follow to avoid musculoskeletal problems derived from bad posture and repetitive movements.